2017
DOI: 10.1097/mao.0000000000001480
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Auditory Evoked Potentials in the Context of Cochlear Implant Provision

Abstract: : Auditory evoked potentials (AEP) are highly demanded during the whole process of equipping patients with cochlear implants (CI). They play an essential role in preoperative diagnostics, intraoperative testing, and postoperative monitoring of auditory performance and success. The versatility of AEP's is essentially enhanced by their property to be evokable by acoustic as well as electric stimuli. Thus, the electric responses of the auditory system following acoustic stimulation and recorded by the conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
18
0
4
Order By: Relevance
“…However, clinical routine suffers from a lack of adequate preoperative measures 22 . Peri‐ and postoperative measures of compound action potentials are currently in the focus of many studies 24,25 . They may potentially explain the remaining variability, yet they apparently cannot contribute to the preoperative counseling of CI candidates.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical routine suffers from a lack of adequate preoperative measures 22 . Peri‐ and postoperative measures of compound action potentials are currently in the focus of many studies 24,25 . They may potentially explain the remaining variability, yet they apparently cannot contribute to the preoperative counseling of CI candidates.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on other ECAP-based clinical application as e.g. described in [ 14 ] is also to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we showed that it is also feasible to record MLRs in CI users elicited by chirp stimuli presented under free-field listening conditions. Because most studies have used electrical stimulation to record MLRs from CI users (Hoth and Dziemba, 2017), the present findings demonstrated the significant potential of the free-field presented chirp stimuli for the evaluation of CIs in clinical settings. However, more studies are needed to properly determine the clinical value of the measures obtained with the chirp stimulus.…”
Section: Chirp Stimuli As a Reliable Alternative To Click Stimuli Formentioning
confidence: 64%